2018
DOI: 10.1002/ece3.4075
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring individual tree‐based change with airborne lidar

Abstract: Understanding the carbon flux of forests is critical for constraining the global carbon cycle and managing forests to mitigate climate change. Monitoring forest growth and mortality rates is critical to this effort, but has been limited in the past, with estimates relying primarily on field surveys. Advances in remote sensing enable the potential to monitor tree growth and mortality across landscapes. This work presents an approach to measure tree growth and loss using multidate lidar campaigns in a high‐bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…Relaxing each of these constraints opens areas of future improvement, especially once species information is available for each label ( Maschler et al, 2018 ). For example, Duncanson and Dubayah, 2018 showed that site-specific allometric functions can be effective at Teakettle Canyon (TEAK) in predicting tree location and measuring growth over time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relaxing each of these constraints opens areas of future improvement, especially once species information is available for each label ( Maschler et al, 2018 ). For example, Duncanson and Dubayah, 2018 showed that site-specific allometric functions can be effective at Teakettle Canyon (TEAK) in predicting tree location and measuring growth over time.…”
Section: Methodsmentioning
confidence: 99%
“…This may be due in part to the point densities of much of NEON’s LiDAR data. Most LiDAR based methods are evaluated on LiDAR data from a single forest type with point densities ranging from ~15 pts/m (e.g., Duncanson and Dubayah, 2018 ) to over 100 pts/m (e.g., Aubry-Kientz et al, 2019 ). In contrast, NEON’s current continental airborne LiDAR program produces ~6 pts/m and these densities can be highly variable, with large areas containing less than 4 pts/m.…”
Section: Methodsmentioning
confidence: 99%
“…There is a critical need to establish standard protocols to produce reproducible, repeatable workflows. Individual tree detection (IDT) is one application of UAS that is imperative for forest management [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Results of this study indicate that sapling identification accuracies can top 90%, and that accuracy improves with the inclusion of red and near infrared spectral bands. Results also indicated that late season imagery performed best when discriminating between young (<5 years) jack pines and herbaceous ground cover in these environments.Drones 2018, 2, 40 2 of 15 as a valid and low-cost method to generate both orthomosaics and digital surface models (DSMs) derived from 2D image sequences [5,6]. In their study of SfM derived IDT, Reference [7] performed ITD using UAS-SfM derived canopy height models based on algorithms designed for LiDAR data processing.…”
mentioning
confidence: 99%
See 1 more Smart Citation